2003
DOI: 10.1097/01.ju.0000067940.76090.73
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in 1,274 European Men Suffering from Lower Urinary Tract Symptoms

Abstract: Erectile dysfunction and reduced ejaculation are highly prevalent in men with lower urinary tract symptoms, and are strongly related to increasing age and lower urinary tract symptom severity. Both these aspects of sexual dysfunction are also highly bothersome, even in advanced age. Sexual function should be carefully assessed in the initial evaluation of patients with lower urinary tract symptoms and in deciding on treatment options, as it may have a negative impact on sex life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
119
5
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(144 citation statements)
references
References 9 publications
15
119
5
5
Order By: Relevance
“…A higher risk of ED has been reported in men using calcium channel antagonist, non-selective b-blocker or diuretic compared with non-users. [7][8][9][10][11] Consistent with other studies, 8,11 we found no increased risk of ED in men using angiotensin-converting enzyme inhibitors or serum lipid-lowering agents.…”
Section: Cardiovascular Drug Use and The Incidence Of Ed R Shiri Et Alsupporting
confidence: 81%
See 1 more Smart Citation
“…A higher risk of ED has been reported in men using calcium channel antagonist, non-selective b-blocker or diuretic compared with non-users. [7][8][9][10][11] Consistent with other studies, 8,11 we found no increased risk of ED in men using angiotensin-converting enzyme inhibitors or serum lipid-lowering agents.…”
Section: Cardiovascular Drug Use and The Incidence Of Ed R Shiri Et Alsupporting
confidence: 81%
“…6 Previous cross-sectional studies have shown associations between heart disease, high blood pressure and their medications use, and ED. 1,5,7 Longitudinal studies have also found a higher incidence of ED in men with hypertension than in those with normal blood pressure. 3,4 In these studies, heart disease was not significantly associated with ED.…”
Section: Introductionmentioning
confidence: 99%
“…28,[30][31][32] In the Multinational Survey of the Aging Male, LUTS were an independent risk factor for ED after controlling for age and comorbidities. 28 We presume that the improvement observed in erectile function in the TURP group in our study was caused by relief of obstructive urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…19 The rates seen in the present study were somewhat higher than the prevalence rates of approximately 40-60% for ED and EjD observed in other studies. 3,[20][21][22][23] It should be noted that these studies had important differences in sample sizes, patient age ranges and the types of questionnaires and survey methods used. Taken together, however, the results of these studies clearly indicate that ED and EjD are common conditions in men with LUTS/BPH.…”
Section: Discussionmentioning
confidence: 99%